1997
DOI: 10.3109/00365519709084595
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for the glomerular filtration rate and cell-proliferation markers: serum cystatin C and serum β2-microglobulin/cystatin C-ratio

Abstract: Recent studies have indicated that serum and plasma cystatin C are better markers for glomerular filtration rate (GFR) than serum creatinine, ubiquitously used for this purpose. To fully exploit the value of serum and plasma cystatin C as GFR markers, reliable age and sex-correlated reference intervals are required. The present study comprised cystatin C determinations in plasma and sera from 259 individuals from a well-defined area in the southernmost part of Sweden. From demographic lists two men and two wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
80
7
10

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 18 publications
14
80
7
10
Order By: Relevance
“…This is consistent with prior reports that demonstrated minimal effects of age on bTP (29,30) or b2M (29) in younger adults (aged ,22 years), but significant associations with age, particularly for b2M, in older adults (31)(32)(33). The positive associations of bTP and b2M with age were also seen with CysC and creatinine, which likely reflect a higher prevalence of decreased GFR with age (27).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is consistent with prior reports that demonstrated minimal effects of age on bTP (29,30) or b2M (29) in younger adults (aged ,22 years), but significant associations with age, particularly for b2M, in older adults (31)(32)(33). The positive associations of bTP and b2M with age were also seen with CysC and creatinine, which likely reflect a higher prevalence of decreased GFR with age (27).…”
Section: Discussionsupporting
confidence: 81%
“…Whereas some studies describe higher bTP concentrations in adult men compared with women (35), most studies have shown no sex differences in children (29,30). b2M has not been shown to differ by sex in youth (29), but some studies have reported higher b2M concentrations in adult men compared with women (33), whereas others report no sex differences (31,32). Our data suggest that men have higher concentrations of bTP than women aged ,30 years and .50 years, whereas serum concentrations of b2M were generally greater in men aged ,40 years.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts to previous work that concluded that cystatin C levels were independent of age in pediatric populations (11,14). Several authors noted an age-related rise in cystatin C levels after the age of 50 to 60 yr (15,32,39), which presumably reflects a decline of kidney function. It is known that there are no changes in GFR during adolescent maturation (40); thus, in this population of generally healthy adolescents aged 12 to 19 yr, the age-related variation in cystatin C levels is likely related to variation in cystatin production.…”
Section: Discussioncontrasting
confidence: 55%
“…These results contradict the older studies which did not recommend establishing sex-related reference values (24,(33)(34)(35)(36)(37), except for results found by Pergande and Jung (38).…”
Section: Physiological Determinants Of Cysc Productioncontrasting
confidence: 56%
“…Caution is however required in very young children and premature infants in whom high CysC values may reflect low GFR as part of the renal maturation process (35,42). Most studies in adults show that age has a significant impact on CysC concentrations, implying different reference values for people over 50-60 years old (30,33,34,37). It is important to note that reference values in both adults and children are systematically lower when measured by the Dade-Behring Siemens PENIA method (vs. the various PETIA applications of the DakoCytomation kit) ( Table 2).…”
Section: Physiological Determinants Of Cysc Productionmentioning
confidence: 99%